A systematic review of the effects of rumination-focused cognitive behavioral therapy in reducing depressive symptoms - Li, Yuyang; Tang, Chunxi (Frontiers in Psychology, 2024)
There is still potential room for improving the effectiveness of standard Cognitive Behavioral Therapy (CBT) in preventing the onset of depression, achieving full remission, and preventing relapse or recurrence of depression. Standard CBT seems less effective in reducing depressive rumination, a key risk factor leading to the onset and persistence of depression. To improve treatment efficacy for depression, rumination-focused cognitive behavioral therapy (RFCBT) was developed, which was modified from CBT and specifically targeted to manage rumination. This systematic review aimed to assess the effects of RFCBT by evaluating whether RFCBT could contribute to reducing depressive symptoms pre-post intervention. A literature search was conducted up to April 30, 2024, across four English-language databases, including PubMed, Web of Science, Google Scholar, and Embase. The search terms employed were: (depress* OR mood OR affect OR rumination) AND ("Rumination Focused Cognitive behavio* Therapy" OR RFCBT). Among the initial 328 studies identified, 12 met the inclusion criteria, of which 10 were randomized controlled trials. Intervention characteristics and results were narratively synthesized to address the review aims. This review found preliminary evidence that the RFCBT could eliminate depressive symptoms post-intervention, and might prevent individuals from developing depression, alleviate depressive symptoms, and prevent relapse of depression, as well as reduce rumination. RFCBT could be promoted to treat depressive symptoms, especially for those with a high tendency towards rumination. However, more studies with rigorous designs are required to confirm its efficacy across different stages of depression. Future studies could compare RFCBT with other psychotherapies, dismantle the psychological therapies to identify their effective components, and explore which specific groups of people might benefit most from this intervention.